2014
DOI: 10.1371/journal.pone.0101590
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hematological Parameters and Insulin Resistance Is Modified by Body Mass Index – Results from the North-East Italy MoMa Population Study

Abstract: ObjectiveIncrements in red blood cell count (RBC), hemoglobin (Hb) and hematocrit (Ht) levels are reportedly associated with higher insulin resistance (IR). Obesity may cause IR, but underlying factors remain incompletely defined, and interactions between obesity, hematological parameters and IR are incompletely understood. We therefore determined whether: 1) BMI and obesity per se are independently associated with higher RBC, hemoglobin and hematocrit; 2) hematological parameters independently predict insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
0
28
0
3
Order By: Relevance
“…Barazzoni et al 32 reported that positive associations among BMI and RBC count, hemoglobin, and hematocrit were dependent on abdominal fat distribution and insulin resistance markers and that obesity per se was not associated with altered hematological parameters. In addition, Sinnapah et al 33 reported that increased RBC aggregation in patients with sleep apnea is caused by being overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Barazzoni et al 32 reported that positive associations among BMI and RBC count, hemoglobin, and hematocrit were dependent on abdominal fat distribution and insulin resistance markers and that obesity per se was not associated with altered hematological parameters. In addition, Sinnapah et al 33 reported that increased RBC aggregation in patients with sleep apnea is caused by being overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Autores já haviam encontrado relação, porém negativa, de IMC e hemoglobina em sul-africanos; entretanto, encontrando relação positiva entre CC e hemoglobina 14 . Outros autores não encontraram relação da CC e do IMC com parâmetros hematológicos em italianos, mas após um ajuste com as variáveis sexo, idade e o hábito de fumar, encontraram uma relação positiva entre eles, o que foi atribuído à gordura abdominal e marcadores de resistência à insulina 6 . Um estudo encontrou uma relação positiva entre CC e hemácias, hemoglobina e hematócrito em americanos voluntários do US National Health and Nutrition Examination Survey (NHANES) 15 .…”
Section: Discussionunclassified
“…Há ainda, a coexistência de ambos estados nutricionais em uma única pessoa, resultado de uma dieta ricamente energética e pobre em micro e macro nutrientes, geralmente encontrada em pessoas carentes 5 . Apesar de não haver consenso entre os pesquisadores, de quais medidas antropométricas seriam positivamente associadas a indicadores hematológicos, há a certeza da importância da avaliação hematológica, junto à presença de obesidade, considerando que ambos influenciam no desenvolvimento de fatores de risco cardiometabólicos, tais como hipertensão e resistência à insulina [6][7] . Assim sendo, o presente estudo objetiva verificar possível associação entre o perfil hematológico e o estado nutricional de trabalhadores e seus filhos.…”
Section: Introductionunclassified
“…Blood cell count is a commonly used and widely available test method and is also associated with type 2 diabetes or obesity to some extent (16)(17)(18)(19) . In addition, in many studies, the use of Mg and serum Mg for disease treatment has been explored based on the relationship between Mg and blood cells (20)(21)(22)(23) .…”
mentioning
confidence: 99%